Safety, security, clean air and intention to experience: Do TikTok short video narratives matter? - Mohammed, I.; Mahmoud, M.A.; Ahmed, A.S.; Preko, A.; Mwin, N.; Clottey, E.K.; Boakye, B. (Tourism and Hospitality Research, 2023)
Safety, security, and clean air have been given some appreciable attention in tourism research and practice. However, little is known about TikTok short video narratives of safety, security, and clean air of a tourism destination. To fill this knowledge gap, this study was guided by narrative transportation theory to examine the impact of TikTok short safety, security, and clean air video narratives on potential tourist intention to experience. The snowball sampling technique was employed to select 357 potential tourists, and the structural equation modelling analysis was utilised to analyse the survey gathered data. The results revealed that there were significant positive associations between short video narratives about safety, security, clean air, and intention to experience. Additionally, the moderating effects of TikTok short video narratives showed a significant positive impact between security, and clean air on intention to experience. Destination marketers and management could utilise TikTok short video narratives in promoting tourism sites through the perspective of tourists.
Research Article
Keywords: Tiktok short video; safety; security; clean air